Community Empowerment through the Application of Tut Wuri Handayani to Organizational Leaders in Indonesia and Malaysia - Ignasius Soni Kurniawan; Umi Wahidah; Ana Fitrotun Nisa; Tri Ratna Purnamarini (Altifani Journal: International Journal of Community Engagement, 2024)
These activities aims to provide an explanation of the application of Tut Wuri Handayani to SME leaders in Yogyakarta consisting of SMEs Pottery & Ceramic Crafts "Dwiyanto Ceramic, UMKM Azka Furniture Bantul, Rama Putra Motor Bantul, and Community Learning Center (CLC) in Malaysia. Community development activity method uses direct and remote observation by utilizing the zoom application with interview techniques. The concept used is the concept of Tut Wuri Handayani to help problems in the field and solutions for leaders in achieving organizational goals. The solution used, holding webinars and training workshops offline and online. The observation results can implement the leadership attitude of Tut Wuri Handayani in the Pottery & Ceramic Craft SME "Dwiyanto Ceramic, UMKM Azka Furniture Bantul, Rama Putra Motor Bantul, and Community Learning Center (CLC).